Comparative Study of Digital Banking Services: User Experience Analysis of BYOND by BSI and BALE by BTN Applications in the Era of Digital Banking Transformation - Nur Milla; Trischa Relanda Putra (Academia Open, 2025)
General Background: The rapid expansion of digital banking in Indonesia has driven banks to develop super apps that integrate financial and lifestyle services. Specific Background: BYOND by BSI and BALE by BTN represent two major innovations reflecting distinct strategic orientations—sharia-based digital integration and lifestyle-oriented financial ecosystems. Knowledge Gap: Despite their rapid adoption, limited comparative studies analyze how these apps differ in user experience, feature effectiveness, and progress toward becoming full super apps. Aims: This study aims to compare BYOND and BALE in terms of service features, security, transactional ease, user satisfaction, and super-app readiness. Results: Findings indicate that BYOND excels in sharia-integrated services and transactional completeness, while BALE performs strongly in mortgage-related features and financial lifestyle support. Both applications are perceived as secure, though concerns over potential data leakage remain. Novelty: This study provides one of the first qualitative comparative analyses of Indonesia’s emerging banking super apps using user-experience-driven evidence. Implications: The results suggest that BYOND is closer to achieving super-app maturity, whereas BALE holds significant potential through ecosystem expansion, offering strategic insights for digital banking development in Indonesia. Highlights: BYOND by BSI excels in integrating financial features and sharia services that are close to the super app concept. BALE by BTN is strong in housing finance and personal financial management services, especially those related to mortgages. Both applications are considered quite secure and facilitate digital transactions, but there are still concerns about data leaks and cyber attacks. Keywords: BYOND by BSI, BALE by BTN, Digital Banking, Super App, Customer Satisfaction, Islamic Banking